Estudo Comparativo de Juntas Soldadas a TIG e Laser Empregando-se Ti com Pureza Comercial Utilizado em Prótese sobre Implantes - Fraga, Alexandre Felix [UNESP] (2007)
Welding in the dentistry has been used for great part of the specialized dentist-surgeons in the implants area to solve prosthesis supported by implant adaptation problems. The development of new equipments Laser and TIG allowed a larger use of these processes in the prosthesis production. In this work, it was studied welded joints made by Laser and TIG, using commercial purity titanium, cpTi, applied in prosthesis supported by implants. The weld characterizations were carried out by light microscopy, EDS_elementary mapping, microhardness and tensile test. Through metallographic characterization, the weld bead presented a martensitic microstructure in the Laser welding process, originated from shear provoked by deformations in the lattice. This caused structural changes of the transformed area, which determines a fine plate-like morphology. In the weld bead from TIG, besides presenting higher hardness, was observed formation of Widmansttaten structure, which is characteristic of a geometric model, resulted of new phase formation along of the crystallographic plans. The martensitic structure is more refined than Widmansttaten structure, due to the high-speed cooling (10(3)degrees C/s) imposed by the Laser process.